PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TINGKATUNDERPRICING IPO (Studi Empiris Pada Perusahaan yang IPO di Bursa Efek Indonesia Tahun 2009- 2014) - Auliya, Reza; Januarti, Indira (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to examine the impact of corporate governance mechanism to level of IPO underpricing.  This study used secondary  data taken from financial  and annually reports one year before company IPO in Indonesia Stock Exchange for years 2009-2014. This study used judgement sampling method. Research population comprise all companies that IPO for the period  2009-2014.  A Total sample  of 105 companies  was used in analysis  from  total population  138 companies.  Hypotheses  in this study indicate that board of commissioner  size, proportion   of  commissioner   independence,   board   of  director   size,   committee   audit   size, institutional ownership, and managerial ownership partially affect the level of underpricing. This study used linier multiple regression analysis for hypotheses testing.  Results of this study showed that the proportion  of commissioner  independence  and committee  audit size positively  affected the level of underpricing.  Board of director had a negative effect on the level of underpricing. This study, did not find significant effects of board of commissioner size, institutional ownership and managerial ownership on the level of IPO underpricing.